1990
DOI: 10.1007/bf00051293
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of trimetazidine in severe ischemic cardiomyopathy

Abstract: The aim of this study was to assess the value of long-term treatment with 60 mg per day of trimetazidine, a cellular antiischemic agent, in comparison with placebo, in patients with ischemic cardiomyopathy controlled by conventional treatments. Twenty patients, with a mean age of 59.5 +/- 1.6 years, suffering from severe ischemic cardiomyopathy (NYHA IV, 6 patients; NYHA III, 14 patients) confirmed by coronary angiography, were included in the study; four of them suffered from residual angina. All of these pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 5 publications
0
8
0
3
Order By: Relevance
“…has shown beneficial effects on ischemic injury. Bricaud et al ( 1990) demonstrated the bene-ficial effect of TMZ in long-term treatment of ischemic cardiomyopathy without associated adverse effect. Bricaud et al ( 1990) demonstrated the bene-ficial effect of TMZ in long-term treatment of ischemic cardiomyopathy without associated adverse effect.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…has shown beneficial effects on ischemic injury. Bricaud et al ( 1990) demonstrated the bene-ficial effect of TMZ in long-term treatment of ischemic cardiomyopathy without associated adverse effect. Bricaud et al ( 1990) demonstrated the bene-ficial effect of TMZ in long-term treatment of ischemic cardiomyopathy without associated adverse effect.…”
Section: Introductionmentioning
confidence: 94%
“…In clinical studies, this drug displayed antianginal properties in improving exercise capacity, total work performed, and electrocardiographic signs of ischemia (Timour et al, 1991;Detry et al, 1994). Bricaud et al ( 1990) demonstrated the bene-ficial effect of TMZ in long-term treatment of ischemic cardiomyopathy without associated adverse effect. Several studies were designed to explain the mechanism of action of this drug.…”
Section: Introductionmentioning
confidence: 99%
“…Bricaud et al. [4] demonstrated the beneficial effect of a long‐term TMZ treatment in ischemic cardiopathy without associated adverse effects. In vitro, the beneficial properties of the molecule were reported in isolated perfused heart models, which confirmed that the mechanism of the beneficial effect was not associated to any haemodynamic component [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Trimetazidine (1-[2,3,4-trimethoxy-benzyl]piperazine 2 HCl; Laboratoires Servier, Courbevoie, France) is an anti-anginal drug devoid of hemodynamic properties. The drug is known for its cardioprotective effects in the treatment of ischemic cardiomyopathy (Bricaud et al, 1990) and was shown to exert its protective effect at the ventricular myocyte level (Lavanchy et al, 1987;Renaud, 1988;Fantini et al, 1994). Several publications reported that the cytoprotective properties of trimetazidine could be partly attributed to an effect on cellular lipid metabolism.…”
mentioning
confidence: 99%